Sorption and desorption of phosphate on biochar and biochar-soil mixtures - Morales, M. M.; Comerford, N.; Guerrini, Iraê Amaral [UNESP]; Falcão, N. P S; Reeves, J. B. (Wiley, 2013)
The term biochar refers to materials with diverse chemical, physical and physicochemical characteristics that have potential as a soil amendment. The purpose of this study was to investigate the P sorption/desorption properties of various slow biochars and one fast pyrolysis biochar and to determine how a fast pyrolysis biochar influences these properties in a degraded tropical soil. The fast pyrolysis biochar was a mixture of three separate biochars: sawdust, elephant grass and sugar cane leaves. Three other biochars were made by slow pyrolysis from three Amazonian tree species (Lacre, Ingá and Embaúba) at three temperatures of formation (400 °C, 500 °C, 600 °C). Inorganic P was added to develop sorption curves and then desorbed to develop desorption curves for all biochar situations. For the slow pyrolysis, the 600 oC biochar had a reduced capacity to sorb P (4-10 times less) relative to those biochars formed at 400 °C and 500 °C. Conversely, biochar from Ingá desorbed the most P. The fast pyrolysis biochar, when mixed with degraded tropical mineral soil, decreased the soil's P sorption capacity by 55% presumably because of the high soluble, inorganic P prevalent in this biochar (909 mg P/kg of biochar). Phosphorus desorption from the fast pyrolysis biochar/soil mixture not only exhibited a common desorption curve but also buffered the soil solution at a value of ca. 0.2 mg/L. This study shows the diversity in P chemistry that can be expected when biochar is a soil amendment and suggests the potential to develop biochars with properties to meet specific objectives. © 2013 British Society of Soil Science.
Keywords: Biochar; Desorption; Phosphorus; Sorption